Do antenatal preparation and obstetric complications and procedures interact to affect birth experience and postnatal mental health? - Hannah Cross; Charlotte Krahé; Helen Spiby; Pauline Slade (BMC, 2023)
Abstract Background Antenatal preparation is commonly offered to women in pregnancy in the United Kingdom, but the content is highly variable, with some programmes orientated towards 'normal birth', whilst others may incorporate information about complications and procedures (broader focus). However, the impact of this variability on birth experience has not been explored. We examined the relationship between the content of antenatal preparation received and birth experience, taking into account obstetric complications and procedures. As birth experience can have a profound impact on a mother's postnatal well-being, we also investigated associations with mothers' postnatal mood and anxiety. Methods N = 253 first-time mothers completed a cross-sectional survey measuring demographic and clinical factors, antenatal preparation content (categorised as normality-focused or broader-focused), obstetric complications and procedures experienced, birth experience (measured using three separate indices; the Childbirth Experience Questionnaire, emotional experiences, and presence/absence of birth trauma), postnatal depression and anxiety, and qualitative information on how the COVID-19 pandemic had affected birth experience. Results Regarding birth experience, receiving more broader-focused preparation was associated with a more positive birth experience irrespective of complications/procedures experienced, while receiving only normality-focused preparation was beneficial in the context of fewer complications/procedures. Regarding birth trauma, receiving more broader-focused preparation was associated with lower likelihood of reporting birth as traumatic only in the context of more complications/procedures. Degree of normality-focused preparation was unrelated to experience of birth trauma. Lastly, while more complications/procedures were associated with greater anxiety and low mood, only greater normality-focused preparation was linked with better postnatal mental health. Conclusions Antenatal preparation including both normality- and broader-focused information is positively related to women's birth experience. While normality-focused preparation seems most beneficial if fewer complications/procedures are experienced, broader-focused preparation may be most beneficial in the context of a greater number of complications/procedures. As complications/procedures are often unpredictable, offering broader-focused preparation routinely is likely to benefit women's birth experience. This antenatal preparation should be freely available and easily accessible.